74. Cerebellum and pain: A transcranial direct current stimulation (tDCS) study. Issue 4 (April 2016) - Bocci, T.; Carli, G.; Santarcangelo, E.; Hesgens, M.; Di Rollo, A.; Barloscio, D.; Parenti, L.; Priori, A.; Valeriani, M.; Sartucci, F.
Abstract : The cerebellum is involved in a wide number of integrative functions, but its role in pain experience is poorly understood. We evaluated the effects of transcranial cerebellar direct current stimulation (tcDCS) by studying the changes in the perceptive threshold, pain intensity (VAS:0-10) and laser evoked potentials (LEPs) variables. Twenty-five subjects were studied before and after anodal, cathodal and sham tcDCS. LEPs were obtained using a Nd:YAP laser and recorded from the dorsum of the left hand. VAS was evaluated by delivering laser pulses at different intensities, respectively two and three times the perceptive threshold. Cathodal polarization dampened significantly the perceptive threshold and increased the VAS score, while the anodal one had opposite effects ( p  < 0.001, two-way repeated measures ANOVA, "time" × "stimulation"). Cathodal tcDCS increased the N1 and N2/P2 amplitudes and decreased their latencies, whereas anodal tcDCS elicited opposite effects ( p  < 0.0001). tcDCS modulates pain perception and its cortical correlates. As it influences both N1 and N2/P2 components, we speculate that the cerebellum modulates the activity of both somatosensory and cingulate cortices. Present findings prompt investigation of the cerebellar direct current polarization as a novel and safe therapeutic tool in chronic pain patients.